Developing a relationship between ore feed grade and flotation performance - Nkadimeng, Mahlogonolo (Department of Chemical Engineering, 2025)
Flotation systems are complex, multifaceted and water-intensive. Prevalent water restrictions globally have made it a necessity for mining operations to recycle onsite process water. This recycling leads to increased ionic strength and may introduce deleterious ions dissolved in solution which affect reagent action, mineral surface properties and pulp chemistry. This may change the water quality over time and may in turn impact plant performance. The depletion of high-grade ore deposits has posed the mining industry with the challenge of processing much more complex, low-grade ores to meet the growing demand of metal production for our technologically driven future. A fundamental understanding of mineral processing is therefore critical for the optimisation of valuable mineral recoveries from such ores. The mineralogy of an ore determines its flotation performance and is thus important to consider. Although evidently critical, ore feed and water quality are in most cases not controlled, therefore rarely investigated. This study seeks to understand the impact of varying ore feed grade(s) on froth stability, gangue recovery and flotation performance using different water qualities. Ionic strength of plant water is defined as water quality in this study. As a means to better understand the impact of varying ore feed grade and water quality , this study considered two synthetic ores; pyrite-based and galena-based synthetic ores. Pyrite and galena were chosen because they are widely studied in the flotation of sulphide ores. Each synthetic ore was analysed in isolation using the same experimental approach to better understand the behaviour(s) of pyrite and galena-based ores with varying feed grades and in a complex water matrix that mimics onsite process water. The experimental approach consisted of batch flotation and froth column tests. Talc, a froth stabilising mineral, was maintained as a constant throughout. The batch flotation tests were carried out to evaluate the effect of varying ore feed grade, water quality and depressant dosage on the overall flotation performance. Froth column tests showed how froth stability, as measured by the froth height and dynamic froth stability, was affected by the changes in ore feed sulphide grade and ionic strength of plant water. In addition, the 3-phase column findings were used to validate the froth stability results obtained from the batch flotation tests. To better understand the effects of depleting ore feed grades and water recycling in flotation, three different ore feed sulphide grades, namely 3, 6 and 12% were considered with a polysaccharide depressant, carboxymethyl cellulose (CMC) at dosages of 0, 100 and 500 g/t, in a complex water matrix consisting of two synthetic plant water types, 3SPW and 10SPW. The simultaneous effects of these variables on solids and water recovery, concentrate iron (Fe) and lead (Pb) grades, froth stability, as well as total gangue recovery in the flotation of the sulphide bearing synthetic ores were investigated. The findings of the pyrite-based synthetic ore showed that the amount of solids and water reporting to the concentrate increased with pyrite feed grade at all depressant dosages and ionic strength of synthetic plant water types. Higher ionic strength of plant water led to higher solids and water recoveries at all depressant dosages and pyrite feed grades, indicating an increase in froth stability owing to a reduction in bubble size and the inhibition of bubble coalescence at high ionic strength of plant water. The 2-phase column findings complemented literature studies and showed that foam height and foam stability increased with the ionic strength of plant water, indicating an enhancement in foam stability by the increased amount of inorganic electrolytes dissolved in the aqueous solution. The 3-phase column findings showed that increasing the ionic strength of synthetic plant water from 3SPW to 10SPW led to an increase in froth height and froth stability at all pyrite feed grades. Furthermore, a simultaneous increase in pyrite feed grade and ionic strength of plant water led to an increase in froth height and froth stability, thereby complementing the froth stability results obtained from batch flotation tests. The introduction of a depressant led to a decrease in the amount of solids and water reporting to the concentrate at all ionic strengths of synthetic plant water and pyrite feed grades. Fe grades increased with pyrite feed grade at all depressant dosages and ionic strength of synthetic plant water. Fe grades also increased concurrently with depressant dosage at all pyrite feed grades and ionic strength of synthetic plant water, with the highest Fe grade generally attained at 500 g/t CMC depressant dosage. Increasing the ionic strength of synthetic plant water led to an increase in Fe grades with pyrite feed grade at all depressant dosages. Furthermore, this work showed that simultaneously increasing pyrite feed grade and ionic strength of synthetic plant water generally had no apparent effect on the Fe recoveries; however, Fe grades increased at all depressant dosages. Galena is a highly hydrophobic sulphide mineral and a major source of commercial lead. The findings of the galena-based synthetic ore showed that the amount of solids reporting to the concentrate increased with increasing galena feed grade at all depressant dosages and ionic strength of synthetic plant water type, while the opposite was true with water recovery, i.e. the amount of water reporting to the concentrate decreased with increasing galena feed grade at all depressant dosages and ionic strength of synthetic plant water. This decrease in water recovery with an increase in galena feed grade was thought to have been owing to the highly hydrophobic mineral component in the feed as the galena feed grade was increased. Solids and water recovery increased as the ionic strength of plant water was increased at all galena feed grades and depressant dosages. The froth column findings showed that froth height and froth stability increased as the ionic strength of plant water type was increased at all galena feed grades. These findings complemented the batch flotation results by further showing that froth height and dynamic froth stability decreased with an increase in galena feed grade at each ionic strength of plant water type. The introduction of a depressant to the galena system led to a decrease in solids and water reporting to the concentrate at all galena feed grades and ionic strength of synthetic plant water types. Pb grades increased with galena feed grade at all depressant dosages and ionic strength of synthetic plant water types. A concurrent increase in Pb grades with depressant dosage was seen at all galena feed grades and ionic strength of plant water. Increasing the ionic strength of synthetic plant water led to an increase in concentrate Pb grades with galena feed grade at all depressant dosages. Simultaneously increasing the galena feed grade and ionic strength of synthetic plant water led to an increase in Pb grades at all depressant dosages, however the Pb recoveries were generally unaffected. This work has demonstrated the need to evaluate the depletion of ore feed sulphide grades in complex water matrices and has shown a relationship between ore feed grade and flotation performance. The knowledge contribution of this study may be key for the mining industry in the quest to addressing environmental degradation and water scarcity issues. Mineral processing plants in which pyrite is a non-valuable mineral may need to implement early mitigation strategies for managing the recovery of pyrite in future as this work has shown there is a greater chance of recovering this mineral as the ores deplete with time. This work has shown that there would still be a greater chance of recovering lead from ores in which lead is the major commercial component mined even at lower feed grades, as such, this kind of knowledge contribution may be a positive for Pb based mining operations. Furthermore, this work has highlighted the use of synthetic ores as proxies for flotation performance under varying ionic strengths of plant water; plant water of higher ionic strengths showed no detrimental effect on flotation performance. Although this may not necessarily represent real industrial conditions, knowledge contributions from this study are a step in the right direction towards developing an understanding into depletion of ore feed grades and degrading water quality on sulphides flotation performance. Findings of this work should be considered for future work and by mineral processing plants which have incorporated a closed-circuit water system in their operations.